Pendidikan Seni: Ilmu Pengetahuan Dalam Ruang Lingkup Penciptaan Karya Tari - Rochayati, Rully (PPSDP Undergraduate Journal of Educational Sciences, 2025)
The purpose of this writing is to find out how arts education is a science within the scope of dance creation. This article presents various perspectives on dance creation from creation methods. The creation of dance art has become part of arts educations taught from midle school to university level. Within this academic scope, the creation of dance works is one of the materials that must be taught with the final result being a dance work. The creative process uses methods based on Western theory and currently the process of creating dance works is starting to be developed which is removed from national ideas, such as the ideas of Ki Hajar Dewantara. The concept of creation and methods as part of the process of creating dance work that are linked to the field of science can be describe in three concept, namely focusing on subject matter/lesson content, focusing on students, based on community needs. When the concept of work and method can be explained on the basis of these three orientations, it is clear that the creation of dance works is part of science.